2021
DOI: 10.3389/fonc.2021.616576
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA FENDRR in Carcinoma-Associated Fibroblasts Regulates the Angiogenesis of Oral Squamous Cell Carcinoma Through the PI3K/AKT Pathway

Abstract: Angiogenesis is essential for the development of tumors. Studies have shown that carcinoma-associated fibroblasts (CAFs) are involved in regulating tumor angiogenesis, but the mechanism remains unclear. Recently, long noncoding RNAs (lncRNAs) have been proved to play an important role in the angiogenesis of various tumors. However, there is currently no research involving the regulation of CAFs on the angiogenesis of oral squamous cell carcinoma (OSCC) mediated by lncRNAs. By analyzing microarray data, we iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In this work, we observed that COL5A1 knockdown suppresses proliferation, migration, invasiveness, and apoptosis resistance of OSCC cells. Moreover, the COL5A1 downregulation also suppressed the angiogenesis activity, which represents a critical factor linking to tumor growth, metastasis, and poor prognosis of patients 21 . In addition, we found that the COL5A1 knockdown limited the growth and metastasis of xenograft tumors formed by OSCC cells.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In this work, we observed that COL5A1 knockdown suppresses proliferation, migration, invasiveness, and apoptosis resistance of OSCC cells. Moreover, the COL5A1 downregulation also suppressed the angiogenesis activity, which represents a critical factor linking to tumor growth, metastasis, and poor prognosis of patients 21 . In addition, we found that the COL5A1 knockdown limited the growth and metastasis of xenograft tumors formed by OSCC cells.…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, the COL5A1 downregulation also suppressed the angiogenesis activity, which represents a critical factor linking to tumor growth, metastasis, and poor prognosis of patients. 21 In addition, we found that the COL5A1 knockdown limited the growth and metastasis of xenograft tumors formed by OSCC cells. These results reveal the oncogenic role of COL5A1 in OSCC.…”
Section: Discussionmentioning
confidence: 78%